Quantification of land use/land cover impacts on stream water quality across Taiwan. (10th October 2021) - Chiang, Li-Chi; Wang, Yung-Chieh; Chen, Yu-Kai; Liao, Ci-Jyun
Abstract: Change in water quality is seen as a reflection of change in terrestrial and aquatic ecosystems that are degraded by anthropogenic activities, including inappropriate land use management, deforestation, and urbanization. As the inter-correlations among landscape structure and ecological process have great influences on the hydrological process, energy flow, and nutrient cycles, it is important to evaluate the impact of landscape configuration on water quality for individual basins. Spatio-temporal variations of water quality and correlations among land use/land cover and water quality across Taiwan have not been thoroughly investigated. In this study, 48 water quality stations within 10 basins across Taiwan are investigated to identify the relationships among various water quality indices, land use/land cover, and landscape metrics at two different time periods. A total of 12 water quality parameters are included: water temperature, pH value, electrical conductivity, dissolved oxygen, biological oxygen demand, chemical oxygen demand, total suspended sediment, total phosphorus, ammonia, nitrate, nitrite, and total nitrogen. Two years (1994 and 2007) of land use/land cover were characterized by using landscape metrics to quantify change in landscape configuration. The hypothesis is that individual basin has different characteristics resulting in different water quality – landscape metric relationships. The results showed that high degrees of landscape fragmentation and interspersion are correlated with degradation of water quality, in terms of high biological and chemical oxygen demands, and nitrogen loads, and such significant relationships are found in certain land use types as pollution sources. Only 3 out of 10 basins have strong or moderate impacts of landscape variation on water quality, indicating these findings could provide reference for developing an effective watershed planning and management with further investigations of landscape configuration at the class level. Highlights: Spatio-temporal variations of water quality are analyzed across Taiwan. Temporal correlations among land use/land cover and water quality are investigated. Temporal variations in landscape metrics of different land use types are evaluated. Landscape metrics variations quantify impacts of land use change on water quality. Water quality–landscape metric relationships give references for land use planning.